A Study of the Working Style of Different Types of Institutes and Attitude of Entrant Science Students of Class XI - Agarwal, P.C.; Agarwal, I.B. (SCHOOL SCIENCE, 2017)
Recent trends show that popularity of coaching institutes for science studies is rapidly increasing and spreading among students and their parents at the entry level of Class XI. There is an increasing tendency of joining coaching institutes after passing out Class X simultaneously with enrolment in dummy schools in Class XI for completion of +2 level science studies. In this study an effort is made to know the reasons why this tendency of entrants to Class XI science subjects of the school system is increasing. A tool is constructed and administered on pass-out students of government and private schools, entrants in coaching institutes and on teachers in these three types of institutes to collect relevant data. The tool covers various dimensions on an experience scale for teachers, students and researchers. A sample of 30 teachers and 60 students of Ajmer district was randomly selected. Various statistical techniques were applied on the collected data. ANOVA test results show that there are no significant mean differences in experiences of teachers, students and researchers regarding various dimensions on the experience scale scores. However, ANOVA test results indicate significant difference in working style of government schools, private schools and coaching institutes which results in increasing tendency in joining coaching institutes.